Waste for Energy Production: Monitoring and Controlling Pollutant Emissions for a Sustainable Economy - Costa, M. A. M. [UNESP]; Albini, G. [UNESP]; Souza, A. J. D. [UNESP]; Oliveira, E. A. [UNESP]; Oliveira, L. F. [UNESP]; Sarti, A. [UNESP]; Dussan, K. J. [UNESP] (Springer Nature, 2025)
IntroductionBiomass offers the advantage of direct application as fuel in furnaces, boilers, or industrial burners. However, while solid biomasses such as sawdust, agricultural waste, and sugarcane bagasse are suitable for pellet production, their combustion emits pollutants, necessitating effective emission control at the source.ObjectiveThis study aims to evaluate and quantify gaseous and particulate emissions from the combustion of sugarcane bagasse and peanut shell pellets, used as industrial fuels.MethodologyCombustion tests were conducted in a pilot-scale burner, with gaseous pollutants and fine particles sampled and quantified. The study evaluated the operating conditions of a pollutant capture device to optimize collection efficiency. A Venturi scrubber was used and evaluated to capture the pollutants emitted by combustion, with special emphasis on collecting particles smaller than 1.0 μm.ResultsThe experimental results demonstrated that the pollutant emission values for sugarcane bagasse and peanut shell pellets were significantly high, particularly for particles with a diameter smaller than 1.0 μm. The average values of diameters sampled during the burning of the fuels vary from 0.2 μm for sugarcane bagasse and 0.4 μm for pellets. The use of pollution control equipment in the collection of particulate matter was very efficient for particles smaller than 1.0 μm. For particles with a diameter of less than 0.056 μm, collection efficiencies reached values above 80%, optimizing the scrubber’s process variables.ConclusionThe use of biomass energy is a relevant alternative in the industrial and energy sectors, but these sources must be controlled and monitored in the search for more sustainable processes.Graphical Abstract